2003
DOI: 10.1016/s0195-668x(02)00655-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte apoptosis is associated with increased wall stress in chronic failing left ventricle

Abstract: Apoptosis of cardiomyocytes in chronic HF is associated with increased wall stress, which may be responsible for the activation of a Fas/FasL and caspase-8 interaction in the region of intercalated discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 36 publications
0
36
0
4
Order By: Relevance
“…There are also many studies demonstrating TUNEL positivity in a small (approximately 0.3%) population of cells in murine CHF models (Jiang et al, 2003). In human samples, the percentage of TUNEL positivity can be higher (up to 2%) (Di Napoli et al, 2003;Hughes, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are also many studies demonstrating TUNEL positivity in a small (approximately 0.3%) population of cells in murine CHF models (Jiang et al, 2003). In human samples, the percentage of TUNEL positivity can be higher (up to 2%) (Di Napoli et al, 2003;Hughes, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the wall stress at the basal segment is higher than at the mid and apical segments because of the nonspherical ventricular geometry and the largest local radius of the LV curvature in the basal part of the septum. 22,23 The propensity to develop increased apoptosis, collagen formation, and subsequent fibrosis might be higher in segments with elevated wall stress, 23 which may partly explain the phenomenon of significantly lower strain values of patients with CA at the basal compared with the apical segments. However, the factor of unequal wall stress is similarly encountered in patients with FD and FA and even more exaggerated in HP, where this additionally leads to significant postsystolic deformation at the basal septum ( Figure 1).…”
Section: Potential Mechanisms Of the Longitudinal Strain Gradientmentioning
confidence: 99%
“…Jiang et al (4) showed a significant relationship between the rate of cardiomyocyte apoptosis, or its regulatory factors, and maladaptive left ventricular remodeling in failing sheep hearts (4). It is not clear if the apoptosis that occurs during myocardial remodeling and HF is a cause or a consequence of cardiac dysfunction.…”
Section: Cell Death Inflammation and Collagen Remodeling Apoptosismentioning
confidence: 99%